Structure and electromechanical properties in Bi0.5Na0.5TiO3-based lead-free piezoceramics with calculated end-member Bi(Ni0.5Ti0.5)O3. Issue 13 (November 2015) - Bai, Wangfeng; Liu, Feng; Li, Peng; Shen, Bo; Zhai, Jiwei; Chen, Haydn
Abstract: The structure of end-member Bi(Ni0.5 Ti0.5 )O3 was calculated by first-principles method and solid solution of the (1 −  x )BNT– x Bi(Ni0.5 Ti0.5 )O3 ((1 −  x )BNT– x BNiT) system was prepared using solid state reaction. Effect of BNiT addition to BNT ceramics on the phase structure, strain behavior, dielectric, ferroelectric, and piezoelectric properties was systematically investigated. The phase diagram was obtained and the relationship between the phase structure and electromechanical properties has been clarified. In comparison to other systems, results in this study indicated a relationship between the morphotropic phase boundary (MPB) composition and tolerance factor and the calculated tetragonality of the end-member Bi(Me′0.5 Me″0.5 )O3, and the t value corresponding to the formation of MPB located in a quite narrow range of 0.975–0.976 in the (1 −  x )BNT– x Bi(Me′0.5 Me″0.5 )O3 systems with low tolerance factor end-members. Thus, this work do not only supplement for BNT-based piezoceramics, but also provide a guideline to predict the approximate MPB region quickly for designing new lead-free piezoelectric ceramics.